2002
DOI: 10.1088/0953-8984/14/12/314
|View full text |Cite
|
Sign up to set email alerts
|

What density-functional theory can tell us about the spin-density wave in Cr

Abstract: The energy-versus-volume curve of the spin-density wave (SDW) in body-centred-cubic Cr is calculated with the density functional theory/full-potential linearized augmented plane wave (DFT/FLAPW) method using the generalized gradient approximation (GGA). The predicted ground state is not the SDW, in contrast to an earlier FLAPW calculation. A conjecture is formulated that the widely varying results of the local density approximation (LDA) and GGA - and of different solution methods - can be scaled by the size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
53
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 24 publications
15
53
1
Order By: Relevance
“…For GGA the antiferromagnetic state exists at an equilibrium lattice constant of 2.87 Å, which is rather close to the experimental value, but the corresponding magnetic moment of 1.02 B is almost twice as large as the experimental one. In principle these lattice constants and magnetic moments should not be comparable to the experimental values since the SDW is known to be the experimental ground state, but previous calculations 21 have shown that the values for simple antiferromagnetic and SDW calculations do not differ too much, justifying the comparison. We can summarize by saying that LDA finds the experimental magnetic moment in the neighborhood of the experimental lattice constant but not at its own equilibrium, while GGA gives a lattice constant comparable with the experimental value but with a magnetic moment that is twice too large: none of both therefore gives a satisfactory description of Cr.…”
Section: Choosing An XC Functionalmentioning
confidence: 88%
See 3 more Smart Citations
“…For GGA the antiferromagnetic state exists at an equilibrium lattice constant of 2.87 Å, which is rather close to the experimental value, but the corresponding magnetic moment of 1.02 B is almost twice as large as the experimental one. In principle these lattice constants and magnetic moments should not be comparable to the experimental values since the SDW is known to be the experimental ground state, but previous calculations 21 have shown that the values for simple antiferromagnetic and SDW calculations do not differ too much, justifying the comparison. We can summarize by saying that LDA finds the experimental magnetic moment in the neighborhood of the experimental lattice constant but not at its own equilibrium, while GGA gives a lattice constant comparable with the experimental value but with a magnetic moment that is twice too large: none of both therefore gives a satisfactory description of Cr.…”
Section: Choosing An XC Functionalmentioning
confidence: 88%
“…For LDA as well as GGA the nonmagnetic and the antiferromagnetic energy-versus-volume curves 8,9,18,21 behave qualitatively identical ͑Fig. 1͒, with a magnetic moment that goes asymptotically to zero for low volumes and a splitting of the two curves at higher volumes, with the antiferromagnetic curve lowest in energy.…”
Section: Choosing An XC Functionalmentioning
confidence: 93%
See 2 more Smart Citations
“…Cr has a bcc crystal structure and exhibits an incommensurate spin-density wave at low temperatures, which is not trivial to properly capture in DFT. [24][25][26] Ni is fcc and displays a ferromagnetic (FM) ordering at low temperatures. This large difference between the properties of the pure elements is responsible for the wide variety of magnetic phases in the ternary phase diagram.…”
Section: Introductionmentioning
confidence: 99%